Kinanthropometric profile, hip bone mineral density, and the incidence of bone stress fractures in professional middle and long-distance runners - Baldyka, J.; Kopiczko, A. (Acta Kinesiologica, 2025)
Purpose: This study aimed to identify the kinanthropometric profile, hip bone mineral density (BMD), and frequency of bone stress fracture (BSF) in professional middle-distance and long-distance runners.